A new disruptive business model for the management consulting industry - Renaud, Pierre (2017)
The world is drastically changing at breakneck speed and global shifts have strong implications on all businesses. The arrival of disruptive innovation is one these major changes. Management consulting firms seem to have a predominant potential to influence the evolution of technology and digitalization. Simultaneously, they are directly affected by these phenomena, and their business strategy needs significant adaptation to integrate these new business aspects. First, they have to change their operation management in an innovative manner. The literature on change management is not sufficient to ensure an efficient transformation. It needs to be associated with new schools of thoughts on disruptive business models. Second, legitimacy and reputation, resulting from institutional capital, have been the two main criteria for clients to choose management consulting services. However, these will not permanently remain as sustainable competitive advantages since clients are able to objectively compare firm services related to technology and digitalization. Third, leaders need to reshape change management towards new disruptive business models. The consideration of diversifying or continuing with existing practices is determining. Deeper integration with society and other stakeholders may help perform better. The world is now more interconnected and each individual committed to management consulting is able to take part in this massive business transformation. The main contribution of this dissertation is to propose a new disruptive business model as a cooperative platform with an innovative framework to cope with disruptive innovation and other arising challenges in the management consulting industry.